180 Cognitive disorders in takotsubo syndrome: incidence, short, and long term outcome. Results from a prospective multi-centre registry. (8th December 2021) - Mallardi, Adriana; Santoro, Francesco; Leopizzi, Alessandra; Vitale, Enrica; Iacoviello, Massimo; Brunetti, Natale Daniele
Abstract: Aims: Takotsubo syndrome (TTS) is an acute and reversible left ventricular dysfunction, whose pathophysiological mechanisms are not completely known. There are evidence suggesting a possible link between neurological disease and TTS. Aim of the study was to evaluate incidence and prognostic value of cognitive neurological disorders among TTS patients. Methods and results: 379 consecutive patients were enrolled in a prospective multicentre registry. History, clinical features, echocardiographic parameters, in-hospital complications and long-term Follow-up events of all patients were recorded. Cognitive neurological disorders included Alzheimer disease, old age dementia and cognitive impairment for other causes. Prevalence of cognitive neurological disorders among TTS patients was 5.5% (num = 21). Among this subset of patients 48% (num = 10) had Alzheimer syndrome, 24% (num = 5) old age dementia and 28% (num = 6) cognitive impairment for other causes. Compared to the control group, these patients were older (81 ± 5 vs. 71 ± 12, P = 0.01) and predominantly men (24% vs. 9%, P = 0.01). No differences in term of cardiovascular risk factors and left ventricular ejection fraction at admission and discharge were found among the two groups. TTS patients with cognitive neurological disorders experienced higher rate of in-hospital complications (62% vs. 28%, P = 0.01), that were mainly driven by higher rate of pulmonary oedema (14% vs. 9%, P = 0.01), cardiogenic shock (29% vs. 8%, P = 0.01), death (24% vs. 4% P = 0.01), ischaemic stroke (10% vs. 4%, P = 0.01), and left ventricular thrombi (10% vs. 3%, P = 0.01). At long-term follow-up patients with cognitive neurological disorders when compared to those without, experienced higher rate of mayor cardiovascular events (48% vs. 16%, P = 0.01), cardiovascular re-hospitalization (14% vs. 10%, P = 0.01) and death (43% vs. 9%, P = 0.01). Conclusions: TTS patients with cognitive neurological disorders had an increased risk of in and out of hospital mayor cardiac adverse events and mortality at short and long-term follow-up.